Discoveries in peripartum cardiomyopathy - Fett, James D.; Markham, David W. (Trends in cardiovascular medicine, 2015)
The past decade has seen remarkable gains for outcomes in peripartum cardiomyopathy (PPCM), one of the leading causes of maternal mortality and morbidity in the USA and many other countries, including the high-incidence areas of Haiti and South Africa. This review article emphasizes the importance of continuing the process of increasing awareness of PPCM and presents details of this evolving picture, including important discoveries that point the way to full recovery for almost all PPCM subjects. In addition, new interventions will be highlighted, which may facilitate recovery. Numerous studies have demonstrated that when the diagnosis of PPCM is made with LVEF > 0.30, the probability is that recovery to LVEF ≥ 0.50 will occur in the overwhelming majority of subjects. PPCM patients diagnosed with severely depressed systolic function (LVEF < 0.30) and a remodeled left ventricle with greater dilatation (LVEDd ≥ 60mm) are least likely to reach the outcome recovery goals. These are the patients with the greatest need for newer interventional strategies.